Fronteiras entre ciência e religião : darwinismo e catolicismo no Brasil dos séculos XIX e XX - Brunah Schall (2014)
Since the publication of The Origin of Species, in 1859, until nowadays Darwin’s ideas about the evolution of species arose many reactions of scientists and religious people around the world. The discussion about the relevance of the idea of evolution led to a debate about the frontiers between science and religion, which were the focus of this work. Brazil took part in this debate, not by introducing original and significant arguments, but by incorporating ideas from foreign intellectuals, which were broadcasted in the popular press. In the research of periodicals found in the portal of Hemeroteca Digital Brasileira and in the digital collection of the journal O Globo it was possible to identify the main characters and contexts involved in the debate, and the most frequent questions that led to the discharge or the integration of the darwinian thought by the catholic thought. Through this questions pervade the ways by which scientists and religious people dispute the authority over knowledge and teaching, and how they define the frontiers between their domains with the purpose of ensuring a power of social influence. However, the opinions of both sides were often mixed, and the frontiers that separated them were modified according to the context. Besides, even when catholics were opposed to darwinism, they kept a favorable vision about science as a whole. In this way, it is proposed that darwinism was not necessarily a topic of a conflict between scientists and religious people, but among those who considered that evolutionary ideas were compatible with religion and those who perceived them as exclusive opposites.